Konflik Sosial: Budaya Politik Uang Di Desa Puguh Kabupaten Kendal Jawa Tengah - Dela Adelia Puspita; Dea Opie Pancaraningrum; Salsabillah Rizqi Fihru Amani Fatikhah (Institut Nalanda, 2023)
Pilkades or Puguh village elections are decorated with politics of money to attract the people's vote, so the politics of money became a normal thing and had become a culture before the village head elections took place. Using an ethnographic approach that focuses on a descriptive development of the political culture of money within a Puguh village community. Results and research discussions of understanding on political money and social conflict. The politics of money itself comes because the elite or prospective village heads seek an influential position in the village, and also because of people who are less conscious of pancasila values and lack of understanding in politically-related communities. In this case the political culture of money itself leads to social conflicts within the society, a conflict of tension in one's interaction with another.